Taxonomy and population genetics of the flightless moth genus, Pringleophaga in the sub-Antarctic - Groenewald, Catharina Wilhelmina (Stellenbosch : Stellenbosch University, 2013)
Thesis (MSc)--Stellenbosch University, 2013.